2001
DOI: 10.1023/a:1010303419034
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Residents' Perceptions of Neighborhood Boundaries: A Methodological Note

Abstract: Neighborhood influences on children and youth are the subjects of increasing numbers of studies, but there is concern that these investigations may be biased, because they typically rely on census-based units as proxies for neighborhoods. This pilot study tested several methods of defining neighborhood units based on maps drawn by residents, and compared the results with census definitions of neighborhoods. When residents' maps were used to create neighborhood boundary definitions, the resulting units covered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
343
0
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(375 citation statements)
references
References 12 publications
(10 reference statements)
13
343
0
12
Order By: Relevance
“…Our measures of segregation employ census tracts as proxies for neighborhoods within MSAs; however, census tracts may not accurately represent residents_ experiences of neighborhood boundaries or the social distance between racial/ethnic groups. 76,77 Finally, our results may reflect selection bias arising from the process through which individuals choose to live in neighborhoods with particular normative or structural characteristics.…”
Section: Discussionmentioning
confidence: 88%
“…Our measures of segregation employ census tracts as proxies for neighborhoods within MSAs; however, census tracts may not accurately represent residents_ experiences of neighborhood boundaries or the social distance between racial/ethnic groups. 76,77 Finally, our results may reflect selection bias arising from the process through which individuals choose to live in neighborhoods with particular normative or structural characteristics.…”
Section: Discussionmentioning
confidence: 88%
“…Studies have reported that perceived and measured features are most highly correlated within small areas, such as one kilometer radial buffers (Moudon et al, 2006, Duncan andMummery, 2005) or zones with 500 residents (Haynes et al, 2007). Investigators have also invited participants to draw their own neighborhood boundaries (Coulton et al, 2001), an approach that may prove important for understanding how people think about the place in which they live. However, the observable heterogeneity in perception offers a crucial challenge for researchers hoping to implement uniform measures.…”
Section: Discussionmentioning
confidence: 99%
“…24 As census tracts boundaries are somewhat artificial and can be subject to the modifiable area unit problem, having the exact location of cases would have been preferable; however, due to confidentiality concerns around HIV this was not possible. 25,26 Therefore, census tracts were used as they were the smallest geographic unit available. They are designed to be stable over time and are considered a preferred unit for geographic analyses when compared to non-population based measures, such as zip codes.…”
Section: Study Populationmentioning
confidence: 99%